Investigation of corrosion effects on galvanized steel-aluminium weld joint - Nur Akmar , Abdul Ariff (2012)
Dissimilar material joining is crucial because it has many advantages but corrosion is become a barrier to this type of joining. The main purpose of this project is to investigate the corrosion effects on galvanized steel-aluminium weld joint by observing its microstructure and to study the optimum parameters that will improve the corrosion behavior of the weld joint. The project scopes are dissimilar welding of galvanized steel-aluminium sheets by using automatic MIG welding; investigate the weld quality, defects and specimen’s microstructure before and after corrosion and lastly investigate the hardness of the weldment. The galvanized steel and aluminium are joined by using varied parameters of voltage and current. Then, the samples had undergone some process for microstructure observation and corrosion test. The polarization test had applied to study the corrosion behavior. The corrosion rate was determined by using Tafel analysis that generated by IVMAN software. The hardness of the weldment is investigated before and after corrosion. The result obtained showed that pitting corrosion take places in almost all sample because of porosity defects during welding process. Besides, the Vickers hardness test showed that there are changes for hardness value after corrosion test. The microstructure showed that sample no. 4 has finer grain structure in fusion zone compared to other sample and has the highest hardness value before and after corrosion. In addition, the corrosion rate is different for all samples and sample no. 4 showed that it has more corrosion resistance. In the nutshell, the heat input used during welding process will have different affect to microstructure and hardness of the weldment. In order to improve this project, the porosity defects which always occur during welding process can be reduced by using low thickness of electrode and used different aqueous solution for corrosion test.